PERAN AUDIT OPERASIONAL PADA UNIT KARYA PENDIDIKAN SEKOLAH DASAR KATOLIK “X” di SUMENEP - Senny Harindahyani (Universitas Bunda Mulia, 2017)
The quality of primary and secondary education in Indonesia is still relatively low, due to low service standards in primary and secondary education accompanied by unchecked corruption within the Department of Education’s bureaucracy. In an effort to improve the quality of schools, there is a need for program evaluation on a regular basis, one of which is operational auditing. The purpose of this research is to gain a extensive understanding of the application of the operational audit in evaluating internal control at Catholic Primary School